The Copenhagen Tool a research tool for evaluation of basic life support educational interventions. (November 2020) - Jensen, Theo Walther; Lockey, Andrew; Perkins, Gavin D.; Granholm, Anders; Eberhard, Kristine E.; Hasselager, Asbjørn; Møller, Thea Palsgaard; Ersbøll, Annette Kjær; Folke, Fredrik; Lippert, Anne; Østergaard, Doris; Handley, Anthony J.; et al.
Abstract: Introduction: Over the past decades, major changes have been made in basic life support (BLS) guidelines and manikin technology. The aim of this study was to develop a BLS evaluation tool based on international expert consensus and contemporary validation to enable more valid comparison of research on BLS educational interventions. Methods: A modern method for collecting validation evidence based on Messick's framework was used. The framework consists of five domains of evidence: content, response process, internal structure, relations with other variables, and consequences. The research tool was developed by collecting content evidence based on international consensus from an expert panel; a modified Delphi process decided items essential for the tool. Agreement was defined as identical ratings by 70% of the experts. Results: The expert panel established consensus on a three-levelled score depending on expected response level: laypersons, first responders, and health care personnel. Three Delphi rounds with 13 experts resulted in 16 "essential" items for laypersons, 21 for first responders, and 22 for health care personnel. This, together with a checklist for planning and reporting educational interventional studies within BLS, serves as an example to be used for researchers. Conclusions: An expert panel agreed on a three-levelled score to assess BLS skills and the included items. Expert panel consensus concluded that the tool serves its purpose and can act to guide improved research comparison on BLS educational interventions.